Magneto-optics of organic crystalline field effect transistors - Ardavan, A; Blundell, S; Singleton, J (2003)
Organic molecular FETs provide an experimental framework for studying the band-filling dependent properties of two-dimensional metals. We propose experiments to investigate the band-filling dependent cyclotron resonance and the effect of van Hove singularities. (C) 2002 Elsevier Science B.V. All rights reserved.